Using Project-Based Learning in Improving Students' Critical Thinking Skills to Separate of Mixtures - Nurul Insani; Noor Fadiawati; Ratu Betta Rudibyani; M. Mahfudz Fauzi Syamsuri (International Journal of Chemistry Education Research, 2018)
Nowadays the development of thinking skills has become the main focus in educational research. Standard of graduate competency mandate that graduates of schools to universities in Indonesia must have thinking skills.  Related to this, the goal of this quasi-experimental study was to describe the effectivity of Project-Based Learning (PjBL) student worksheets to improve students' critical thinking skills (CTS) in the topic of mixtures separation. This study was carried out in the SMPN 1 Pugung by using the Non-Equivalent (Pretest-Posttest) Control Group Design. The effectivity of PjBL student worksheets measured based on the n-gain and the effect size values. Statistically, the n-gain value of the experimental class was higher than the control class. The effect size value was in medium categorized.  These results indicated that the PjBL student worksheets were effective to improve students' CTS in the topic of mixtures separation. Keywords: student worksheets, project-based learning, critical thinking skills, mixtures separation